Making the most of food aid to help prevent child and maternal deaths - Cogill, Bruce (Johns Hopkins School Bloomberg School of Public Health, Center for Communication Programs, 2013)
Advances in child nutrition over the last several decades are creating momentum for a programmatic push to reduce undernutrition worldwide. The contribution of food aid may be small, but, nonetheless, U.S. food aid policy should be revamped to benefit more effectively and more efficiently the children and mothers in need.